Negative plate and lithium ion battery

By coating the inactive substance coating on both sides of the negative electrode sheet of the lithium-ion battery and using the inactive substances with the extreme ear glue layer, the risk of thermal runaway caused by the polarization of the lithium-ion battery during rapid charging is solved, and the circulation performance and energy density of the battery are improved.

CN119890219AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411995732.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the fast charging process, lithium-ion batteries may experience greater polarization, resulting in an increase in the growth of lithium dendrites and the risk of thermal runaway. How to reduce the safety risks of batteries is an important research direction for the development of battery technology.

Method used

A negative electrode sheet is provided, and the edges of both sides are coated with a coating containing inactive substances, reducing the generation of lithium and lithium dendrites at the edge of the negative electrode, improving the edge lithium descent window, and reducing the risk of thermal runaway caused by lithium dendrites piercing the diaphragm. At the same time, the electrode glue layer containing inactive substances is used to replace the traditional electrode protection glue, reduce the overall thickness of the battery cell, improve the energy density, and reduce the risk of lithium-ion edge lithium.

Benefits of technology

By reducing the generation of lithium and lithium dendrites at the negative electrode edge, the risk of thermal runaway in lithium-ion batteries is reduced, and the circulation performance and energy density of the batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890219A_ABST
    Figure CN119890219A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a negative plate and a lithium ion battery. In the width direction of the negative plate, the negative active material layer comprises a first coating and a second coating on two side edges; the first coating and the second coating independently comprise a first inactive material; and / or the negative plate comprises a tab; a lug groove is formed in the surface of at least one side of the negative current collector; the tab glue layer covers the tab groove, and the tab glue layer comprises a second inactive substance; the first inactive substance and the second inactive substance independently comprise at least one of polyimide, polyetherimide and polyamide-imide. According to the negative plate, lithium precipitation at the edge of the negative plate and generation of lithium dendrites can be reduced, an edge lithium precipitation window is improved, the thermal runaway risk caused by the fact that the lithium dendrites pierce the diaphragm is reduced, and the cycle performance of the battery is improved; and the negative plate uses the tab glue layer containing the inactive substance to replace the traditional tab protection glue, so that the overall thickness of the battery cell can be reduced, and the energy density can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode sheet and a lithium ion battery. Background Art

[0002] With the rapid development of electric vehicles and smart devices, higher requirements are placed on the fast charging capabilities of batteries. Fast charging can significantly shorten the charging time and improve user experience, and is an important direction for the development of the battery industry. During the fast charging process, a large polarization may occur inside the battery, leading to the growth of lithium dendrites and an increased risk of thermal runaway. How to reduce the safety risks of batteries is an important research direction for the development of battery technology. Summary of the invention

[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art, and to provide a negative electrode sheet and a lithium-ion battery including the negative electrode sheet. The edges of both sides of the negative electrode sheet are coated with an inactive substance, which can reduce the formation of lithium deposition and lithium dendrites at the edge of the negative electrode, increase the edge lithium deposition window, reduce the risk of thermal runaway caused by lithium dendrites piercing the diaphragm, and improve the cycle performance of the battery; and / or, the negative electrode sheet uses a tab glue layer containing an inactive substance to replace the traditional tab protective glue, which can reduce the overall thickness of the battery cell, increase the energy density, and reduce the risk of lithium deposition at the tab edge.

[0004] In order to achieve the above-mentioned object, the first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector, and a negative electrode active material layer disposed on two opposite side surfaces of the negative electrode current collector; in the width direction of the negative electrode sheet, the negative electrode active material layer comprises a first coating area and a second coating area at two side edges; the first coating area is provided with a first coating layer, and the second coating area is provided with a second coating layer; the first coating layer and the second coating layer independently comprise a first inactive substance; the first inactive substance comprises at least one of polyimide, polyetherimide, and polyamide-imide;

[0005] And / or, the negative electrode sheet includes a pole lug, the pole lug protrudes from one side of the negative electrode current collector in the width direction, and the pole lug is electrically connected to the negative electrode current collector; a pole lug groove is provided on the surface of at least one side of the negative electrode current collector, and the bottom of the pole lug groove exposes the negative electrode current collector; the pole lug includes a first pole lug area and a second pole lug area extending out of the pole lug groove, and the first pole lug area is located in the pole lug groove; the negative electrode sheet includes a pole lug glue layer, the pole lug glue layer covers the pole lug groove, and the pole lug glue layer includes a second inactive substance; the second inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

[0006] A second aspect of the present invention provides a lithium ion battery, the battery comprising the negative electrode sheet described in the first aspect of the present invention.

[0007] In some embodiments, the battery includes a wound cell, the wound cell includes a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet, the separator and the positive electrode sheet are sequentially stacked and wound along the length direction from one end to form the wound cell;

[0008] The wound-type battery cell includes an arc region and a straight region extending between the arc regions, wherein the arc region includes a first arc region and a second arc region; along the width direction of the wound-type battery cell, the positive electrode sheet includes a first arc segment and a second arc segment located at the outermost ends; the first arc segment is located in the first arc region, and the second arc segment is located in the second arc region;

[0009] The outermost circle of the wound battery cell is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector, and a first positive electrode active layer and a second positive electrode active layer arranged on two opposite sides of the positive electrode current collector in the thickness direction; along the winding direction of the wound battery cell, the tail end of the first positive electrode active layer exceeds the tail end of the second positive electrode active layer to form a double-sided positive electrode region and a single-sided positive electrode region;

[0010] The positive electrode sheet in the first arc segment is a single-sided positive electrode area, and the positive electrode sheet in the second arc segment is a hollow foil area; a third coating is provided on the surface of the single-sided positive electrode area in the first arc segment away from the negative electrode sheet; and / or a fourth coating is provided on the surface of the hollow foil area in the second arc segment away from the negative electrode sheet;

[0011] The third coating layer and / or the fourth coating layer independently include a third inactive substance; the third inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

[0012] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0013] (1) In the negative electrode sheet provided by the present invention, the edges of both sides of the negative electrode sheet are coated with a coating containing an inactive substance, which can reduce the formation of lithium deposition and lithium dendrites at the edge of the negative electrode, increase the edge lithium deposition window, reduce the risk of thermal runaway caused by lithium dendrites piercing the diaphragm, and improve the cycle performance of the battery;

[0014] (2) In the negative electrode sheet provided by the present invention, the conventional tab protective glue (insulating tape) is replaced by a tab glue layer containing an inactive substance, which can reduce the overall thickness of the battery cell, improve the energy density, and reduce the risk of lithium deposition at the tab edge.

[0015] (2) In the lithium-ion battery provided by the present invention, an inactive substance is further coated on the surface of the outermost positive electrode sheet in the arc region, which can reduce material damage and structural destruction caused by mechanical stress, reduce battery cell deformation, and improve the structural stability and cycle performance of the battery.

[0016] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Shown is a schematic structural diagram of a cross section of a wound-type battery cell in an example of the present invention.

[0018] Figure 2 Shown is a schematic structural diagram of a vertical cross section of a wound-type battery cell in an example of the present invention.

[0019] Figure 3 Shown along Figure 4 Schematic diagram of the AA cross section, the edge area of ​​the negative electrode sheet is coated with the first coating and the second coating.

[0020] Figure 4 The figure shows a schematic top view of a first coating and a second coating applied to the edge area of ​​a negative electrode sheet in an example of the present invention.

[0021] Figure 5 The figure shows a cross-sectional schematic diagram of coating the third coating and the fourth coating on the arc area of ​​the positive electrode sheet in one example of the present invention.

[0022] Figure 6 The figure shows a rear view schematic diagram of coating the third coating and the fourth coating on the arc area of ​​the positive electrode sheet in one example of the present invention.

[0023] Figure 7 The figure shows a cross-sectional schematic diagram of a tab glue layer coated on a negative electrode tab protection area in an example of the present invention.

[0024] Figure 8 The figure is a top view schematic diagram of the tab glue layer coated on the negative electrode tab protection area in one example of the present invention.

[0025] Fig. 9 Shown is an infrared spectrum of PI glue in an example of the present invention.

[0026] Figure numerals: 1-positive electrode sheet; 11-positive electrode current collector; 12-first positive electrode active layer; 13-second positive electrode active layer; 14-first arc segment; 141-third coating layer; 15-second arc segment; 151-fourth coating layer; 2-negative electrode sheet; 21-negative electrode current collector; 22-negative electrode active material layer; 221-first coating layer; 222-second coating layer; 3-diaphragm; 4-ear; 41-first ear region; 42-second ear region; 5-ear groove; 6-ear glue layer. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0028] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0029] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0030] In the present invention, the term "inactive substances" refers to substances that do not participate in electrochemical reactions during the charge and discharge process of the battery, and these substances may hinder the transmission of lithium ions.

[0031] A first aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising: a negative electrode current collector, and a negative electrode active material layer disposed on two opposite sides of the negative electrode current collector;

[0032] In the width direction of the negative electrode sheet, the negative electrode active material layer includes a first coating area and a second coating area at both side edges; the first coating area is provided with a first coating layer, and the second coating area is provided with a second coating layer; the first coating layer and the second coating layer independently include a first inactive material; the first inactive material includes at least one of polyimide, polyetherimide, and polyamide-imide;

[0033] And / or, the negative electrode sheet includes a pole lug, the pole lug protrudes from one side of the negative electrode current collector in the width direction, and the pole lug is electrically connected to the negative electrode current collector; a pole lug groove is provided on the surface of at least one side of the negative electrode current collector, and the bottom of the pole lug groove exposes the negative electrode current collector; the pole lug includes a first pole lug area and a second pole lug area extending out of the pole lug groove, and the first pole lug area is located in the pole lug groove; the negative electrode sheet includes a pole lug glue layer, the pole lug glue layer covers the pole lug groove, and the pole lug glue layer includes a second inactive substance; the second inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

[0034] In the present invention, a first coating layer and a second coating layer comprising a first inactive substance are coated on both side edges of the negative electrode sheet, and the first coating layer and the second coating layer are coated on the surface of the negative electrode active substance layer. On the one hand, the interface side reaction between the electrolyte and the negative electrode surface is weakened, the transmission rate of lithium ions in the edge area is directionally regulated, the transmission of lithium ions in the edge area of ​​the negative electrode sheet is hindered or isolated, the lithium precipitation window is improved, the formation of lithium dendrites and lithium precipitation at the edge of the negative electrode is reduced, and the risk of thermal runaway caused by lithium dendrites piercing the diaphragm is reduced; on the other hand, since the first inactive substance has good adhesion, mechanical properties and thermal stability, the volume expansion of the negative electrode can be suppressed, and the structural integrity of the electrode and the cycle life of the battery are improved.

[0035] In addition, in the present invention, the tab glue layer containing the second inactive substance is coated in the tab groove, which can replace the traditional tab protective glue, reduce the overall thickness of the battery cell, improve the energy density, and reduce the risk of lithium plating at the tab edge.

[0036] In some embodiments, the first coating layer and the second coating layer independently include a first inactive substance, that is, the inactive substance coated in the first coating layer and the inactive substance in the second coating layer may be the same or different, preferably the same.

[0037] In some embodiments, the pore size D1 of the first coating and the second coating is independently 0.5nm to 1.5nm, for example, independently 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1.0nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm or any point value in the range composed of the above two point values. The pore size of the first coating and the second coating may be the same or different. When the pore size of the first coating and the second coating is within the above range, the transmission rate of lithium ions in the edge area of ​​the negative electrode sheet can be regulated by adjusting the pore size, further improving the problem of lithium plating in the electrode sheet and improving the capacity retention rate during the cycle.

[0038] In some embodiments, Figure 3 and Figure 4As shown, the negative electrode sheet 2 includes a negative electrode current collector 21, and a negative electrode active material layer 22 disposed on the opposite side surfaces of the negative electrode current collector 21. In the width direction of the negative electrode sheet 2, the negative electrode active material layer 22 includes a first coating area and a second coating area at the edges of both sides; the first coating area is provided with a first coating 221, and the width of the first coating 221 is d1 and the thickness is h1. The second coating area is provided with a second coating 222, and the width of the second coating 222 is d2 and the thickness is h2. The coating of inactive substances in the first coating and the second coating can reduce the formation of lithium deposition and lithium dendrites at the edge of the negative electrode, and reduce the risk of thermal runaway caused by lithium dendrites piercing the diaphragm.

[0039] In some embodiments, in the width direction of the negative electrode sheet, the width d1 of the first coating is 0.1mm-15mm, and d1 can be, for example, 0.1mm, 1mm, 2mm, 4mm, 5mm, 6mm, 8mm, 10mm, 12mm, 14mm, 15mm or any point value in the range composed of the above two point values. The width d2 of the second coating is 0.1mm-15mm, and d2 can be, for example, 0.1mm, 1mm, 2mm, 4mm, 5mm, 6mm, 8mm, 10mm, 12mm, 14mm, 15mm or any point value in the range composed of the above two point values. The width d1 of the first coating and the width d2 of the second coating can be the same or different, preferably the same. When the width d1 of the first coating and the width d2 of the second coating are in the above range, it is avoided that the inactive material is coated too wide, resulting in a reduction in the effective utilization area of ​​the active material and a reduction in the capacity of the battery.

[0040] In some embodiments, in the thickness direction of the negative electrode sheet, the thickness h1 of the first coating is 0.1 μm-10 μm, and h1 can be, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any point value in the range of the above two point values. The thickness h2 of the second coating is 0.1 μm-10 μm, and h2 can be, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any point value in the range of the above two point values. The thickness h1 of the first coating and the thickness h2 of the second coating can be the same or different, preferably the same. When the thickness h1 of the first coating layer and the thickness h2 of the second coating layer are within the above range, it is possible to avoid the coating layer being too thick, which may cause uneven volume changes of the battery during charging and discharging, thereby causing damage to the electrode structure and shortening the cycle life of the battery; and to avoid the coating layer being too thin, which may fail to effectively prevent the transmission of lithium ions in the edge area, and improve the poor effect of negative electrode lithium deposition.

[0041] In some embodiments, in the length direction of the negative electrode sheet, the length of the first coating layer is less than or equal to the length of the negative electrode sheet, and the length of the second coating layer is less than or equal to the length of the negative electrode sheet. Preferably, the length of the first coating layer is equal to the length of the negative electrode sheet, and the length of the second coating layer is equal to the length of the negative electrode sheet.

[0042] In some embodiments, the negative electrode sheet includes a pole lug, which protrudes from one side of the negative electrode current collector in the width direction, and the pole lug is electrically connected to the negative electrode current collector; a pole lug groove is provided on the surface of at least one side of the negative electrode current collector, and the bottom of the pole lug groove exposes the negative electrode current collector; the pole lug includes a first pole lug area and a second pole lug area extending out of the pole lug groove, and the first pole lug area is located in the pole lug groove; the negative electrode sheet includes a pole lug glue layer, the pole lug glue layer covers the pole lug groove, and the pole lug glue layer includes a second inactive substance; the second inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

[0043] In some embodiments, Figure 7 and Figure 8 As shown, a pole lug 4 is provided on one side of the width direction of the negative electrode sheet, and the pole lug 4 protrudes from one side of the width direction of the negative electrode current collector 21, and a pole lug groove 5 is provided at the edge of the negative electrode current collector 21 near the pole lug 4. The pole lug 4 includes a first pole lug area 41 and a second pole lug area 42, the first pole lug area 41 is located in the pole lug groove 5, and the second pole lug area 42 extends out of the pole lug groove 5. The surface of the pole lug groove 5 is covered with a pole lug glue layer 6, and the size of the pole lug glue layer 6 is larger than the size of the pole lug groove 5.

[0044] In some embodiments, in the width direction of the negative electrode sheet, the size d5 of the tab glue layer is 0.1 mm-15 mm, and d5 can be, for example, 0.1 mm, 1 mm, 2 mm, 4 mm, 5 mm, 6 mm, 8 mm, 10 mm, 12 mm, 14 mm, 15 mm, or any point value in the range of the above two point values. In the thickness direction of the negative electrode sheet, the thickness h5 of the tab glue layer is 0.5 μm-20 μm, and h5 can be, for example, 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, or any point value in the range of the above two point values. The present invention adopts a tab glue layer containing a third inactive substance to replace the traditional tab protective glue (insulating tape). The thickness of the tab glue layer is less than the thickness of the insulating tape (>20μm), which can reduce the overall thickness of the battery cell, improve the energy density, and reduce the risk of lithium plating at the tab edge.

[0045] In some embodiments, in the length direction of the negative electrode sheet, the size of the tab glue layer is greater than or equal to the size of the tab slot; in the width direction of the negative electrode sheet, the size of the tab glue layer is greater than or equal to the size of the tab slot. The size of the tab glue layer is greater than the size of the tab slot, which can ensure that the tab glue layer completely covers the tab slot, so as to effectively isolate the tab from contact with the outside world and prevent the occurrence of a short circuit.

[0046] In some embodiments, the first inactive substance and the second inactive substance may be the same or different.

[0047] In some embodiments, the first inactive substance includes polyimide glue; and / or the second inactive substance includes polyimide glue.

[0048] Preferably, the first inactive substance is polyimide glue (PI), and the second inactive substance is polyimide glue. Polyimide glue can hinder or isolate the transmission of lithium ions in the negative electrode plate, reducing negative electrode lithium deposition; and polyimide glue has high mechanical properties and thermal stability, can reduce battery deformation, improve the structural stability of the battery, and comprehensively improve the safety performance and cycle performance of the battery.

[0049] In some embodiments, the chemical formula of the polyimide glue is [-R1-CO-NH-R2-CO-] n , R1 and R2 represent different dibasic anhydride and diamine groups respectively, n is the degree of polymerization, indicating the number of repeating units, and the value range of n is 40-720.

[0050] In some embodiments, the polyimide glue can be prepared or purchased. Exemplarily, the polyimide glue can be prepared by a solution polycondensation method, wherein a dibasic anhydride and a diamine are subjected to a polycondensation reaction in a polar solvent to generate a polyimide acid, and then dehydrated and cyclized by heating or chemical methods to form a polyimide glue (PI). The dibasic anhydride includes at least one of pyromellitic anhydride, cyclobutane tetracarboxylic anhydride, hexafluoroisopropylphthalic anhydride, maleic anhydride, and acetic anhydride, and the diamine includes at least one of 1,2-diaminopropane, diphenylethylenediamine, o-phenylenediamine, m-phenylenediamine, and p-phenylenediamine.

[0051] In some embodiments, by designing and synthesizing cross-linked dianhydrides, the micropore size of the polyimide glue coating network, that is, the pore size of the upper coating, can be adjusted, thereby regulating the transmission rate of lithium ions on the electrode sheet, reducing the pore size of the coating, and thereby reducing the lithium ion transmission in the edge area and arc area of ​​the negative electrode sheet, thereby reducing lithium plating at the negative electrode.

[0052] In some embodiments, the infrared spectrum of the polyimide glue is as follows: Fig. 9 As shown in Figure 2, the characteristic peaks of the infrared spectrum of polyimide glue are related to the structure of its chemical groups. The infrared spectrum shows the following characteristic peaks: Imidazole ring characteristic peak: at about 1400 cm-1 It appears at 1634cm, representing the CN vibration in the azole ring; the characteristic peak of imide bonding: -1 appears at 3309cm, representing the C=O vibration of imide; -1 It appears at about 1457 cm, representing the NH vibration of imide; the characteristic peak of benzene ring: -1 It appears at , representing the C=C vibration of the benzene ring.

[0053] In some embodiments, the glass transition temperature (Tg) of the polyimide glue is 200°C-430°C, for example, 200°C, 220°C, 250°C, 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, 420°C, 430°C or any point value in the range of any two of the above points. Adjusting the Tg of the polyimide glue can improve the flexibility of the negative electrode sheet, easily buffer the deformation of the battery cell during the cycle process, improve the stability of the battery structure, and help the battery maintain efficient ion transmission during the charge and discharge process, thereby improving the energy density.

[0054] In some embodiments, the specific surface areas of the first coating layer, the second coating layer, and the tab glue layer are independently 280 to 700 m 2 When the specific surface areas of the first coating layer, the second coating layer and the ear glue layer are within the above range, the transmission of lithium ions can be appropriately promoted, and the purple spots caused by the complete obstruction of lithium ion transmission can be reduced.

[0055] In some embodiments, the first inactive material and the second inactive material are independently grafted with sulfur-containing groups. In the area where the inactive material is normally coated, the lithium ion transmission rate is low. If the lithium ion transmission rate is too low, purple spots will appear on the electrode. In the present invention, by grafting specific groups on the inactive material, sulfur has high electronegativity and can react with lithium ions (Li + ) produces a strong electrostatic attraction, which helps to accelerate the transmission of lithium ions and avoid purple spots on the electrode caused by slow lithium ion transmission.

[0056] Preferably, the content of S element in the first coating, the second coating and the tab glue layer is independently 0.05-0.6%. When the S element is within the above range, the barrier effect of the coating containing the inactive substance on the transmission of lithium ions can be moderate, thereby avoiding lithium deposition on the pole piece due to excessively fast lithium ion transmission rate and avoiding purple spots on the pole piece due to excessively low lithium ion transmission rate.

[0057] In some embodiments, the sulfur-containing group includes at least one of a sulfonic acid group (—SO 3 H), a thiol group (—SH), a sulfoxide group (—SO—R), and a thioketone group (—C(═S)—SR).

[0058] The test method for the content of S element includes: weighing 0.5g sample, adding 5ml HNO3, heating and digesting at 350℃ for 10min, cooling and filtering, fixing the volume to 50ml, and using inductively coupled plasma optical emission spectrometer ICP-OES to test and obtain the result.

[0059] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon material; preferably, in the negative electrode active material, the mass proportion of silicon element is 3%-85%, for example, it can be 3%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 85%, preferably 5%-40%. The silicon negative electrode has the advantage of high gram capacity, which is beneficial to improve the energy density of the battery. However, since the negative electrode prepared from silicon material is prone to expansion, lithium deposition and battery cell deformation are prone to occur. The present invention can reduce lithium deposition at the edge of the negative electrode by arranging the first coating and the second coating in the edge area, and the third coating and the fourth coating in the arc area can reduce the deformation caused by the expansion of the silicon negative electrode, inhibit the volume expansion of silicon particles, and improve the structural integrity of the electrode and the cycle life of the battery.

[0060] The test method for the mass percentage of silicon element includes: in the negative electrode active material, the mass percentage of silicon element can be obtained by acid treatment of the negative electrode active material and then ICP analysis calculation. Alternatively, the test method for the mass percentage of silicon element can be tested by thermogravimetric analysis, for example, using Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions are: sample amount 5 mg, air as atmosphere, heating rate 10℃ / min from room temperature to 900℃ and constant temperature for 40 minutes. The relationship between the mass percentage of silicon-carbon material (x) and the final weight residual percentage (y) of the entire test is: x=7y / 15.

[0061] In some embodiments, the silicon material includes at least one of silicon oxygen, silicon carbon, nano silicon, and silicon alloy.

[0062] In some embodiments, the thickness of the negative electrode sheet is 40 μm-200 μm, for example, 40 μm, 50 μm, 60 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm. When the thickness of the negative electrode sheet is within the above range, the risk of internal short circuit of the battery due to the negative electrode sheet being too thin can be avoided, and the negative electrode sheet being too thick can be avoided to affect the diffusion rate of lithium ions and the charge and discharge performance of the battery.

[0063] In some embodiments, the porosity of the negative electrode sheet is 25%-65%. When the porosity of the negative electrode sheet is within the above range, sufficient electrolyte infiltration and rapid diffusion of lithium ions can be ensured while reducing lithium deposition at the negative electrode.

[0064] In the present invention, the porosity can be obtained by gas adsorption method (BET method) test, and the specific test method is: weigh the sample, install the sample tube and the analysis port Dewar flask; set the gas cylinder pressure reducer to 15-18psia (0.1Mpa), and the vacuum pump provides a vacuum degree less than 20μm; fill the Dewar with liquid nitrogen to complete the degassing treatment; start analysis and output the analysis result list file, calculate the pore volume and pore size distribution, and then obtain the porosity.

[0065] In some embodiments, the negative electrode current collector may be at least one of copper foil, nickel foil, composite current collector or carbon-based current collector. The middle layer of the composite current collector is organic (such as polymer materials such as PET / PP / PI), and the upper and lower layers are copper-plated or aluminum-plated layers. A carbon-based current collector refers to a current collector based on carbon materials (such as carbon nanotubes, graphene, carbon fibers, etc.). The thickness of the negative electrode current collector is 4μm-10μm. The negative electrode current collector can improve its electrochemical properties by surface coating. Carbon coating the surface of the negative electrode current collector can provide additional conductivity and mechanical stability, reduce the crushing of silicon materials during volume expansion, and thus improve the cycle stability of the battery.

[0066] In some embodiments, the negative electrode active material layer includes a binder, and the binder includes at least one of carboxymethyl cellulose salt, polyacrylic acid, polyacrylate, styrene-butadiene rubber, styrene-acrylic rubber, polyurethane, polyvinyl pyrrolidone, polyaniline, polyamide-imide, polysiloxane, epoxy resin, polyester resin, polyurethane resin or polyfluorene. The mass percentage of the binder in the negative electrode active material layer is 0.5% to 12%.

[0067] In some embodiments, the negative electrode active material layer includes a conductive agent, which includes at least one of conductive carbon black, Ketjen black, conductive graphite, graphene, carbon aerogel, MXene material, three-dimensional mesoporous carbon, carbon nanotubes or carbon fibers, and the mass percentage of the conductive agent in the negative electrode active material layer is 0.01% to 10%.

[0068] In some embodiments, the negative electrode active material layer includes a thickener, and the thickener includes at least one of lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, hydroxypropyl methyl cellulose, and hydroxyethyl cellulose.

[0069] In some embodiments, the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener in the negative electrode active material layer may be (90.2-97.8):(0.05-10):(1.2-8):(0.2-1), or any other suitable mass ratio may be used.

[0070] A second aspect of the present invention provides a lithium ion secondary battery, the battery comprising the negative electrode sheet described in the first aspect of the present invention.

[0071] The battery provided by the present invention, because it includes the above-mentioned negative electrode sheet, has the advantages of less lithium deposition, good safety performance and good cycle performance.

[0072] In some embodiments, the battery comprises a wound cell, the wound cell comprising a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet, the separator and the positive electrode sheet are sequentially stacked and wound along the length direction from one end to form the wound cell. Figure 1 As shown, a wound battery cell comprises a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3. The positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 are stacked in sequence and wound from one end along the length direction to form a wound battery cell.

[0073] In some embodiments, the battery includes a wound cell, the wound cell includes a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet, the separator and the positive electrode sheet are sequentially stacked and wound along the length direction from one end to form the wound cell;

[0074] The wound-type battery cell includes an arc region and a straight region extending between the arc regions, wherein the arc region includes a first arc region and a second arc region; along the width direction of the wound-type battery cell, the positive electrode sheet includes a first arc segment and a second arc segment located at the outermost ends; the first arc segment is located in the first arc region, and the second arc segment is located in the second arc region;

[0075] The outermost circle of the wound battery cell is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector, and a first positive electrode active layer and a second positive electrode active layer arranged on two opposite sides of the positive electrode current collector in the thickness direction; along the winding direction of the wound battery cell, the tail end of the first positive electrode active layer exceeds the tail end of the second positive electrode active layer to form a double-sided positive electrode region and a single-sided positive electrode region;

[0076] The positive electrode sheet in the first arc segment is a single-sided positive electrode area, and the positive electrode sheet in the second arc segment is a hollow foil area; a third coating is provided on the surface of the single-sided positive electrode area in the first arc segment away from the negative electrode sheet; and / or a fourth coating is provided on the surface of the hollow foil area in the second arc segment away from the negative electrode sheet;

[0077] The third coating layer and / or the fourth coating layer independently include a third inactive substance; the third inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

[0078] In some embodiments, a third coating is provided on the surface of the positive electrode collector of the single-sided positive electrode area in the first arc segment away from the negative electrode sheet; a fourth coating is provided on the surface of the positive electrode collector of the hollow foil area in the second arc segment away from the negative electrode sheet. Alternatively, the third coating is provided only on the surface of the single-sided positive electrode area in the first arc segment away from the negative electrode sheet; or, the fourth coating is provided only on the surface of the hollow foil area in the second arc segment away from the negative electrode sheet. Preferably, the third coating and the fourth coating are provided at the same time, so that the surface of the positive electrode collector of the outermost positive electrode sheet in the arc area of ​​the wound battery cell is coated with an inactive substance. The inactive substance has good mechanical properties and thermal stability, can better withstand the volume expansion and contraction during the battery charge and discharge process, reduce material damage and structural damage caused by mechanical stress, reduce battery cell deformation, and improve the structural stability and cycle performance of the battery.

[0079] In some embodiments, the pore size D2 of the third coating and / or the fourth coating is independently 0.5nm to 1.5nm, for example, independently 0.5nm, 0.6nm, 0.7nm, 0.8nm, 0.9nm, 1.0nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm or any point value in the range composed of any two of the above point values. The pore sizes of the third coating and the fourth coating may be the same or different. When the pore sizes of the third coating and the fourth coating are within the above range, the internal stress of the battery during expansion can be dispersed, the deformation of the arc area of ​​the winding core can be reduced, the structural stability of the battery can be improved, and the cycle performance of the battery can be improved.

[0080] In some embodiments, the method for testing the pore size in the first coating, the second coating, the third coating, and the fourth coating includes using an atomic force microscope (AFM), mounting the sample on the sample stage of the AFM device, selecting a suitable scanning mode, and analyzing parameters such as pore size, pore structure, and pore size distribution through the AFM image.

[0081] In some embodiments, Figure 1 and Figure 2 As shown, the wound cell includes an arc region and a straight region extending between the arc regions, and the arc region includes a first arc region and a second arc region; in the width direction of the winding core, the positive electrode sheet includes a first arc segment 14 and a second arc segment 15 away from the straight region; the first arc segment 14 is located in the first arc region, and the second arc segment 15 is located in the second arc region. The surface of the positive electrode collector in the first arc segment 14 is provided with a third coating 141; the surface of the positive electrode collector in the second arc segment 15 is provided with a fourth coating 151.

[0082] In some embodiments, Figure 1 , Figure 5 and Figure 6As shown, the positive electrode sheet 1 includes a positive electrode collector 11, and a first positive electrode active layer 12 and a second positive electrode active layer 13 arranged on the opposite side surfaces of the positive electrode collector 11 in the thickness direction; along the length direction of the positive electrode sheet, the tail end of the first positive electrode active layer 12 exceeds the tail end of the second positive electrode active layer 13. Along the length direction of the positive electrode sheet 1, a third coating 141 is arranged on the first arc segment 14, and the width of the third coating 141 is d3 and the thickness is h3. A fourth coating 151 is arranged on the second arc segment 15, and the width of the fourth coating 151 is d4 and the thickness is h4. The coating of inactive substances in the third coating and the fourth coating can reduce the deformation of the battery cell and improve the structural stability and cycle performance of the battery.

[0083] In some embodiments, in the length direction of the positive electrode sheet, the size d3 (width d3) of the third coating is 0.1mm-15mm, and d3 can be, for example, 0.1mm, 1mm, 2mm, 4mm, 5mm, 6mm, 8mm, 10mm, 12mm, 14mm, 15mm or any point value in the range composed of the above two point values. The size d4 of the fourth coating is 0.1mm-15mm, and d4 can be, for example, 0.1mm, 1mm, 2mm, 4mm, 5mm, 6mm, 8mm, 10mm, 12mm, 14mm, 15mm or any point value in the range composed of the above two point values. The width d3 of the third coating and the width d4 of the fourth coating can be the same or different, preferably the same. When the width d3 of the third coating and the width d4 of the fourth coating are in the above range, it is avoided that the inactive material is coated too wide, resulting in an increase in the volume of the battery cell and a reduction in the overall energy density.

[0084] In some embodiments, in the thickness direction of the positive electrode sheet, the thickness h3 of the third coating is 0.1 μm-10 μm, and h3 can be, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any point value in the range of the above two point values. The thickness h4 of the fourth coating is 0.1 μm-10 μm, and h4 can be, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any point value in the range of the above two point values. The thickness h3 of the third coating and the thickness h4 of the fourth coating can be the same or different, preferably the same. When the thickness h3 of the third coating and the thickness h4 of the fourth coating are in the above range, it is avoided that the coating layer is too thick, resulting in uneven volume change of the battery during charging and discharging, thereby causing damage to the electrode structure and shortening the cycle life of the battery.

[0085] In some embodiments, in terms of the width of the positive electrode sheet, the size of the third coating layer is ≤ the width of the positive electrode sheet (i.e., the length of the third coating layer is ≤ the width of the positive electrode sheet). The size of the fourth coating layer is ≤ the width of the positive electrode sheet (i.e., the length of the fourth coating layer is ≤ the width of the positive electrode sheet). Preferably, the length of the third coating layer is equal to the width of the positive electrode sheet, and the length of the fourth coating layer is equal to the width of the positive electrode sheet.

[0086] In some embodiments, d1=d2<d3=d4, that is, the width of the first coating d1=the width of the second coating d2, the width of the third coating d3=the width of the fourth coating d4, and the width of the first coating (or the second coating) is smaller than the width of the third coating (or the fourth coating), that is, the size of the inactive material coated on the edge area is smaller than the size of the inactive material coated on the arc area, which can not only reduce lithium plating at the edge of the negative electrode, improve the safety performance of the battery and the energy density of the battery, but also reduce the deformation of the battery cell, improve the stability of the battery structure, and enhance the capacity retention rate and cycle performance of the battery.

[0087] In some embodiments, the first inactive substance, the second inactive substance, and the third inactive substance may be the same or different.

[0088] In some embodiments, the third inactive material includes polyimide glue. Polyimide glue has high mechanical properties and thermal stability, can reduce battery cell deformation, improve battery structural stability, and comprehensively improve battery safety and cycle performance.

[0089] In some embodiments, the specific surface area of ​​the third coating and the fourth coating is independently 280 m 2 / g~700m 2 When the specific surface area of ​​the third coating layer and the fourth coating layer is within the above range, a uniform and effective covering layer can be formed on the surface of the winding core, so that when the battery core is subjected to external mechanical forces such as extrusion or collision, the deformation of the battery core structure can be reduced.

[0090] In some embodiments, the battery further includes a positive electrode sheet and a separator, wherein the positive electrode sheet and the negative electrode sheet are separated by the separator disposed therebetween, while allowing lithium ions to pass therethrough, thereby preventing the battery from overheating.

[0091] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, and the positive electrode active material layer is located on one side or both sides of the positive electrode current collector. The positive electrode current collector can be aluminum foil or other positive electrode current collectors commonly used in the art. The thickness of the positive electrode current collector can be 1μm-15μm. The positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material may include at least one of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium iron phosphate (LFP), a ternary material (nickel cobalt manganese oxide (NCM) and nickel cobalt aluminum oxide (NCA)), lithium aluminate or lithium manganate. The conductive agent includes at least one of conductive carbon black, conductive graphite, graphene or carbon nanotubes. The binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, a styrene-acrylate copolymer, a styrene-butadiene copolymer, a polyamide, a polyacrylonitrile, a polyacrylate, a polyacrylic acid, a polyacrylate, a polyvinyl acetate, a polyvinylpyrrolidone, a polyvinyl ether, a polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The mass ratio of the positive active material, the conductive agent and the binder in the positive active material layer is (95-98.5): (0.1-3): (0.1-5), and any other suitable mass ratio may also be used.

[0092] In some embodiments, the isolation membrane includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyethylene terephthalate, polyimide or aramid. The thickness of the isolation membrane is 3μm-12μm. The surface of the isolation membrane may also include a porous layer, which is arranged on at least one surface of the isolation membrane, and the porous layer includes inorganic particles and a binder, and the inorganic particles are selected from aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The pore size range of the pores in the isolation membrane is 0.01μm-1μm. The binder of the porous layer includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, carboxymethyl cellulose salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene.

[0093] In some embodiments, the lithium ion secondary battery further includes an electrolyte, and the electrolyte includes a non-aqueous solvent and a lithium salt.

[0094] Exemplarily, the non-aqueous solvent includes a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be at least one of a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof. The lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, the concentration of the lithium salt being 1 mol / L to 2 mol / L, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate being 0.06-5. The electrolyte may also include a non-aqueous solvent.

[0095] The electrolyte includes at least one of fluoroether, fluoroethylene carbonate or ether nitrile.

[0096] Exemplarily, the chain carbonate compound includes at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and a combination thereof. The cyclic carbonate compound includes at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or a combination thereof. The fluorinated carbonate compound includes fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or a combination thereof. The carboxylate compound includes at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone, mevalonolactone, caprolactone, methyl formate or a combination thereof. The ether compound includes at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran or a combination thereof. Other organic solvents include at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate or a combination thereof.

[0097] The lithium ion secondary battery of the present invention can be used in any electronic device known in the prior art. The electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, an unmanned aerial vehicle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium ion capacitor.

[0098] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0099] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0100] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0101] The batteries of the examples and comparative examples were prepared according to the following preparation methods.

[0102] Example 1-1:

[0103] (1) Preparation of negative electrode sheet:

[0104] The negative electrode active material artificial graphite, SiC, binder lithium polyacrylate, carbon nanotubes and lithium carboxymethyl cellulose are dissolved in deionized water at a weight ratio of 87.03:9.67:2.0:0.6:0.7 to form a negative electrode slurry. The negative electrode slurry is coated on both sides of the negative electrode current collector copper foil (thickness of 6μm) with a coating thickness of 76μm. After drying, cold pressing and slitting, the negative electrode sheet is obtained, and the silicon content is 9%.

[0105] PI glue coating: Apply PI glue evenly on the edge area of ​​the negative electrode. Figure 3 and Figure 4 As shown, the coating width d1 = d2 = 6.2 mm, the coating thickness h1 = h2 = 4.3 mm, the pore size D1 of the PI glue is 0.8 nm, and the specific surface area of ​​the PI glue is BET530 m 2 / g, the glass transition temperature Tg of PI glue is 312℃.

[0106] (2) Preparation of positive electrode sheet:

[0107] The positive electrode active material lithium cobalt oxide, conductive agent conductive graphite, and binder polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) solution at a weight ratio of 97.2:1.1:1.7 to form a positive electrode slurry. An 8μm thick aluminum foil is used as the positive electrode current collector, and the positive electrode slurry is coated on both sides of the positive electrode current collector with a coating thickness of 49μm. After drying, cold pressing, and slitting, the positive electrode sheet is obtained.

[0108] (3) Preparation of isolation membrane: The isolation membrane substrate is 7 μm thick polyethylene (PE), and a 2 μm alumina ceramic layer is coated on both sides of the isolation membrane substrate. Finally, a 2 μm adhesive polyvinylidene fluoride (PVDF) is coated on both sides of the ceramic layer and dried.

[0109] (4) Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): polypropylene (PP): diethyl carbonate (DEC) = 1:1:1:1, mass percentage) were prepared into an electrolyte with a lithium salt concentration of 1.05 mol / L.

[0110] (5) Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, with the separator placed between the positive and negative electrodes to isolate them, and wind them to obtain an electrode assembly (wound-type battery cell). Place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte and package it, and obtain a lithium-ion battery through a process of formation, degassing, shaping, and capacity separation.

[0111] The batteries obtained in the examples and comparative examples were subjected to the following performance tests:

[0112] (i) Lithium deposition test

[0113] At 25°C, charge the lithium-ion battery to 4.5V at a constant current of X (X = 1, 2, 3) C, then charge to 0.05C at a constant voltage of 4.5V and let stand for 5 minutes; then discharge to 3.0V at a constant current of 1C and let stand for 5 minutes. This is a cycle. After repeating 10 cycles, disassemble the battery in a fully charged state to obtain the negative electrode sheet. If any area of ​​the negative electrode sheet relative to the PI coating area is greater than or equal to 2mm 2 If lithium is deposited in the area of ​​​​the negative electrode, it is determined to be lithium deposited on the negative electrode sheet, and the unit is C. The higher the lithium deposition level, the lower the degree of lithium deposition at the same charging rate.

[0114] (ii) Energy density test

[0115] At 25°C, the lithium-ion battery (finished lithium-ion battery after formation) was charged to 4.5V at 1C constant current, left for 10 minutes, and discharged to a cut-off voltage of 3.0V at 1C constant current (5 batteries per group) to obtain the energy of the lithium-ion battery. The energy density of a lithium-ion battery (Wh / L) = the energy of the lithium-ion battery / the volume of the lithium-ion battery.

[0116] (iii) 25℃ Cyclic Performance Test

[0117] Test the sample voltage, internal resistance, thickness and DC internal resistance at 25℃±5℃;

[0118] ①Stand at 25℃±2℃ for 10min;

[0119] ②0.2C discharge to the lower limit voltage, let stand for 10 minutes;

[0120] ③ Charge at 0.7C to the upper limit voltage, cut off at 0.025C, and let stand for 10 minutes;

[0121] ④0.2C discharge to the lower limit voltage; (for initial capacity test);

[0122] ⑤Let stand for 10 minutes;

[0123] ⑥2C charge 4.25V (cut off 1.5C) 1.5C charge 4.3V (cut off 1C) 1C charge 4.5V (cut off 0.25C) Test the first full charge data, voltage, internal resistance, thickness, DC internal resistance;

[0124] ⑦Stand at 25℃±2℃ for 10min;

[0125] ⑧0.7C discharge to the lower limit voltage; let stand for 10 minutes;

[0126] ⑨2C charge to 4.25V (cut-off 1.5C) 1.5C charge to 4.3V (cut-off 1C) 1C charge to 4.5V (cut-off 0.25C), let stand for 10 minutes;

[0127] ⑩ Repeat steps 8 to 9 500 times and record the test results.

[0128] The examples 1 to 3 were carried out in accordance with the example 1-1, and the main differences are shown in Table 1. In the example 1, the aperture D1 of the first coating layer and the second coating layer was changed; in the example 2, the width d1 of the first coating layer and the width d2 of the second coating layer were changed; in the example 3, the thickness h1 of the first coating layer and the thickness h2 of the second coating layer were changed.

[0129] Table 1

[0130]

[0131]

[0132] It can be seen from Table 1 that by coating the first coating layer and the second coating layer containing PI glue on the edges of both sides of the negative electrode sheet and adjusting the pore size, width and thickness of the first coating layer and the second coating layer within the protection scope of the present invention, the edge lithium precipitation window can be increased, the capacity retention rate of the battery can be improved and the cycle expansion rate can be reduced.

[0133] The Example 4 and Comparative Example 1 were carried out with reference to Example 1-1, and the main differences are shown in Table 2. In the Example 4, the tab glue was applied to the tab groove, while in Example 1-1, a traditional acrylic tape with a thickness of 15 μm was attached to the tab groove. Among them, the thickness of the tab glue layer was changed in Examples 4-1 to 4-4; in Example 4-5, the first coating layer and the second coating layer were not provided, and only the tab glue layer was provided; in Comparative Example 1, the first coating layer and the second coating layer were not provided, and neither the tab glue layer was provided.

[0134] Table 2

[0135]

[0136] It can be seen from Table 2 that coating the tab glue layer containing PI in the tab groove instead of the traditional tab protective glue can increase the high energy density of the battery, improve the edge lithium precipitation window, improve the capacity retention rate of the battery and reduce the cycle expansion rate.

[0137] The examples 5 to 7 were carried out with reference to the examples 1 to 1, with the main differences shown in Table 3. In the example 5, PI glues with different glass transition temperatures were selected; in the example 6, PI glues with different specific surface areas and pore sizes were selected in the first coating layer and the second coating layer (the two were the same); in the example 7, PI glue was grafted with sulfonic acid groups, and the S element content was changed.

[0138] Table 3

[0139]

[0140] It can be seen from Table 3 that when the glass transition temperature, specific surface area and pore size of the PI glue in the first coating and the second coating are in an appropriate range, the edge lithium precipitation window can be increased, the capacity retention rate of the battery can be improved, and the cycle expansion rate can be reduced. In addition, when the PI glue is grafted with sulfur-containing groups to control the S element content in an appropriate range, the edge lithium precipitation window can be increased, the capacity retention rate of the battery can be improved, and the cycle expansion rate can be reduced.

[0141] The examples 8-10 and 11 are carried out with reference to the example 1-1. On the basis of the example 1-1, the PI glue is applied to the arcs on both sides of the outermost side of the winding core. The main differences are shown in Table 4. In the example 8, the aperture D2 of the third coating layer and the fourth coating layer is changed; in the example 9, the width d3 of the third coating layer and the width d4 of the fourth coating layer are changed; in the example 10, the thickness h3 of the third coating layer and the thickness h4 of the fourth coating layer are changed; in the example 11, d1=d2>d3=d4 are set, and the width of the arc area coating is smaller than that of the edge area coating.

[0142] Table 4

[0143]

[0144]

[0145] It can be seen from Table 4 that coating PI on the arc surfaces on both sides of the outermost layer of the wound battery can release the internal stress caused by expansion and reduce damage, reduce cell deformation, improve the battery's cycle capacity retention rate and reduce the cycle expansion rate.

[0146] Example 12 was carried out with reference to Example 8-1, and the main differences are shown in Table 5. In Example 12, PI glues with different glass transition temperatures were selected.

[0147] Table 5

[0148]

[0149] It can be seen from Table 5 that when the glass transition temperature of the PI glue in the third coating and the fourth coating is in an appropriate range, the edge lithium precipitation window can be increased, the capacity retention rate of the battery can be improved, and the cycle expansion rate can be reduced.

[0150] The Example 13 group was carried out with reference to the Example 8-1, and the main differences are shown in Table 6. In the Example 13 group, the silicon content in the negative electrode active material and the type of silicon material were changed.

[0151] Table 6

[0152]

[0153]

[0154] It can be seen from Table 6 that setting the first coating and the second coating at the edge area of ​​the negative electrode sheet can reduce lithium plating at the edge of the negative electrode and reduce the lithium plating window. Setting the third coating and the fourth coating in the arc area outside the winding core can reduce the deformation caused by the expansion of the silicon negative electrode, improve the capacity retention rate of the battery and reduce the cycle expansion rate.

[0155] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0156] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet comprises: a negative electrode current collector, and a negative electrode active material layer disposed on two opposite sides of the negative electrode current collector; In the width direction of the negative electrode sheet, the negative electrode active material layer includes a first coating area and a second coating area at both side edges; the first coating area is provided with a first coating layer, and the second coating area is provided with a second coating layer; the first coating layer and the second coating layer independently include a first inactive material; the first inactive material includes at least one of polyimide, polyetherimide, and polyamide-imide; And / or, the negative electrode sheet includes a pole lug, the pole lug protrudes from one side of the negative electrode current collector in the width direction, and the pole lug is electrically connected to the negative electrode current collector; a pole lug groove is provided on the surface of at least one side of the negative electrode current collector, and the bottom of the pole lug groove exposes the negative electrode current collector; the pole lug includes a first pole lug area and a second pole lug area extending out of the pole lug groove, and the first pole lug area is located in the pole lug groove; the negative electrode sheet includes a pole lug glue layer, the pole lug glue layer covers the pole lug groove, and the pole lug glue layer includes a second inactive substance; the second inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide.

2. The negative electrode sheet according to claim 1, characterized in that: The pore diameters D1 of the first coating layer and the second coating layer are independently 0.5 nm to 1.5 nm.

3. The negative electrode sheet according to claim 1, characterized in that: In the width direction of the negative electrode sheet, the width d1 of the first coating layer is 0.1 mm-15 mm, and the width d2 of the second coating layer is 0.1 mm-15 mm; And / or, in the thickness direction of the negative electrode sheet, the thickness h1 of the first coating layer is 0.1 μm-10 μm, and the thickness h2 of the second coating layer is 0.1 μm-10 μm; And / or, in the length direction of the negative electrode sheet, the length of the first coating layer is ≤ the length of the negative electrode sheet, and the length of the second coating layer is ≤ the length of the negative electrode sheet.

4. The negative electrode sheet according to claim 1, characterized in that: In the width direction of the negative electrode sheet, the dimension d5 of the tab glue layer is 0.1 mm-15 mm; And / or, in the thickness direction of the negative electrode sheet, the thickness h5 of the tab glue layer is 0.5 μm-20 μm; And / or, in the length direction of the negative electrode sheet, the size of the tab glue layer is ≥ the size of the tab groove; in the width direction of the negative electrode sheet, the size of the tab glue layer is ≥ the size of the tab groove.

5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The first inactive substance includes polyimide glue; and / or the second inactive substance includes polyimide glue; Preferably, the glass transition temperature of the polyimide glue is 200°C-430°C; Preferably, the specific surface area of ​​the first coating, the second coating, and the tab glue layer is independently 280 m 2 / g~700m 2 / g.

6. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The first inactive substance and / or the second inactive substance are independently grafted with a group containing a sulfur element; Preferably, the content of S element in the first coating, the second coating and the tab glue layer is independently 0.05%-0.6%; Preferably, the sulfur-containing group includes at least one of a sulfonic acid group, a thiol group, a sulfoxide group, and a thione group.

7. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes a silicon material; Preferably, in the negative electrode active material, the mass percentage of silicon element is 3%-85%; Preferably, the silicon material includes at least one of silicon oxygen, silicon carbon, nano silicon, and silicon alloy; Preferably, the thickness of the negative electrode sheet is 40 μm-200 μm; and / or the porosity of the negative electrode sheet is 25%-65%.

8. A lithium ion battery, characterized in that: The battery comprises the negative electrode sheet according to any one of claims 1 to 7.

9. The battery according to claim 8, characterized in that The battery comprises a wound cell, wherein the wound cell comprises a negative electrode sheet, a positive electrode sheet and a separator, wherein the negative electrode sheet, the separator and the positive electrode sheet are sequentially stacked and wound along a length direction from one end to form the wound cell; The wound-type battery cell includes an arc region and a straight region extending between the arc regions, wherein the arc region includes a first arc region and a second arc region; along the width direction of the wound-type battery cell, the positive electrode sheet includes a first arc segment and a second arc segment located at the outermost ends; the first arc segment is located in the first arc region, and the second arc segment is located in the second arc region; The outermost circle of the wound battery cell is a positive electrode sheet, and the positive electrode sheet includes a positive electrode current collector, and a first positive electrode active layer and a second positive electrode active layer arranged on two opposite sides of the positive electrode current collector in the thickness direction; along the winding direction of the wound battery cell, the tail end of the first positive electrode active layer exceeds the tail end of the second positive electrode active layer to form a double-sided positive electrode area and a single-sided positive electrode area; The positive electrode sheet in the first arc segment is a single-sided positive electrode area, and the positive electrode sheet in the second arc segment is a hollow foil area; a third coating is provided on the surface of the single-sided positive electrode area in the first arc segment away from the negative electrode sheet; and / or a fourth coating is provided on the surface of the hollow foil area in the second arc segment away from the negative electrode sheet; The third coating and / or the fourth coating independently include a third inactive substance; the third inactive substance includes at least one of polyimide, polyetherimide, and polyamide-imide; Preferably, the pore size D2 of the third coating layer and / or the fourth coating layer is independently 0.5 nm to 1.5 nm.

10. The battery according to claim 9, characterized in that In the length direction of the negative electrode sheet, the size d3 of the third coating layer and / or the size d4 of the fourth coating layer are independently 0.1 mm to 15 mm; And / or, in the thickness direction of the negative electrode sheet, the thickness h3 of the third coating layer and / or the thickness h4 of the fourth coating layer is 0.1 μm-10 μm; And / or, in terms of the width of the negative electrode sheet, the size of the third coating layer is ≤ the width of the negative electrode sheet, and / or the size of the fourth coating layer is ≤ the width of the negative electrode sheet; Preferably, d1=d2<d3=d4.

11. The battery according to claim 9 or 10, characterized in that: The third inactive substance includes polyimide glue; And / or, the specific surface area of ​​the third coating and the fourth coating is independently 280m 2 / g~700m 2 / g.

Citation Information

Patent Citations

  • Secondary battery

    CN107579190A

  • Polyimide-coated modified lithium ion battery negative electrode active material, preparation method and application

    CN115000364A

  • Adhesive tape for lithium battery tab, cathode plate, battery cell structure and lithium battery

    CN218101627U

  • Electrode plate and battery comprising same

    CN219534554U

  • Lithium ion secondary battery

    WO2019093226A1

Cited By

  • Battery, battery pack and electric equipment

    CN121529124A